Transformasi Layanan Informasi Publik dengan Metode Digitalisasi Melalui Pengembangan Website Kecamatan Arut Selatan - Delia Marsya Azura; Rotzami Rotzami; Ardieansyah Ardieansyah (Lembaga Pengembangan Kinerja Dosen, 2025)
Fast, transparent, and easily accessible public services are the primary needs of the community in supporting effective regional development. Arut Selatan District, Kotawaringin Barat Regency, realizes the importance of digital transformation in improving the quality of public information services. The development of a sub-district profile website called SAKTI (Integrated Sub-district Administration System Service) was initiated as an effort to digitize public information services to facilitate public access to various administrative and information services provided by the sub-district. This internship report aims to document the process of developing and evaluating the implementation of the SAKTI website as an innovation in public services based on information technology. using direct observation methods, implementing website development, documenting administrative activities, and interviewing employees and community users of the service. The evaluation was carried out by referring to laws and regulations related to public services and information technology, as well as analyzing the obstacles faced during the implementation process. Results: Producing a final product that the SAKTI website has a positive impact on increasing service transparency and accelerating public access to public administration information. However, infrastructure constraints such as limited internet connections that are not evenly distributed and low digital literacy in the community are significant obstacles to optimal use of the website. In addition, website management and maintenance require increased human resource capacity in the sub-district so that service sustainability can be maintained. This report confirms that digitalization of services through websites is a strategic step to support more efficient and inclusive public services at the sub-district level. Continuous support is needed in the form of improving technological infrastructure, digital literacy training for the community and sub-district employees, and professional website management so that this innovation can provide maximum benefits to the wider community.